Adverse effects and non-adherence to antihypertensive medications in University of Gondar Comprehensive Specialized Hospital - Eyob Alemayehu Gebreyohannes; Akshaya Srikanth Bhagavathula; Tamrat Befekadu Abebe; Yonas Getaye Tefera; Tadesse Melaku Abegaz (BMC, 2019)
Abstract Background A considerable proportion of cardiovascular events could be attributed to poor adherence to antihypertensive medications. Adverse effects can be severe enough to affect adherence to antihypertensive medications. This study aimed to measure the contribution of adverse effects on antihypertensive medications adherence. Methods The study was conducted from May 1 to June 30, 2017, at the ambulatory clinic of University of Gondar Comprehensive Specialized Hospital (UOGCSH) in Gondar town. A binary logistic regression was performed to determine the significance of the association between adverse effects and adherence to antihypertensive medications. An institution-based cross-sectional study was conducted by administering a questionnaire to hypertensive patients who came for follow-up at the ambulatory clinic of UOGCSH. Level of adherence to antihypertensive medications was used as outcome measure. Results A total of 249 patients were included in the final analysis with a mean age of 56.51 years and a female majority (53%). The following variables were identified as predictors of poor adherence: tiredness [AOR (95% CI): 3.802 (1.723-8.391), p = 0.001], muscle pain [AOR (95% CI): 5.199 (1.407-19.214), p = 0.013], poor sleep [AOR (95% CI): 4.891 (1.578-15.160), p = 0.006] and, believing that the symptoms were caused by antihypertensive medications [AOR (95% CI): 3.249 (1.248-8.456), p = 0.016]. Conclusion Adverse effect significantly contributes to antihypertensive medication non-adherence among hypertensive patients.